IMPLEMENTASI MANAJEMEN RISIKO KEPATUHAN SYARIAH PADA KOPERASI SYARIAH (STUDI LITERATUR DAN IMPLIKASI PADA GAKOPSYAH BMT JAWA BARAT) - Tria Najiatul Rohmah; Gina Sakinah (PT. Hasba Edukasi Mandiri, 2025)
This study examines the implementation of sharia compliance risk management in Islamic cooperatives with a case study on Gakopsyah BMT Jawa Barat. The main focus is on potential risks arising from discrepancies between practice and sharia principles, strategies for risk management, and the role of the Sharia Supervisory Board (DPS) in ensuring compliance. The findings indicate that major risks occur in the implementation of contracts such as murabahah and mudharabah, which are vulnerable to violations if not managed properly. To address these challenges, Gakopsyah BMT Jawa Barat has developed sharia-based standard operating procedures (SOPs), strengthened internal sharia audits, and optimized the role of DPS as both supervisor and advisor. In addition, members’ sharia literacy and the adoption of digital technology are crucial supporting factors in enhancing compliance systems. By consistently applying risk management, Gakopsyah BMT Jawa Barat is able to maintain its reputation, increase members’ trust, and strengthen sustainability as a competitive Islamic cooperative.